The Analysis of Health Social Security Agency (BPJS) and the Indonesia Health Card (KIS) Services at Setiabudi Public Health Center, South Jakarta - Purwaningtias, Agitta Sofyan (Lembaga Penerbitan Universitas Esa Unggul, 2021)
There are several phenomena at Setiabudi Public Health Center, South Jakarta City that attracts the researcher's attention. The public health center is lacking health service, administrative service, low call alert, and unfriendly when dealing with patients. In addition, a very long queue often happen which leads to the patient less comfortable and laziness to wait. In addition, not all drugs are covered by the Indonesia Health Card. Therefore, patients have to buy drugs outside of the public health center. The Doctor only serves for two minutes, The Public Health Center officers are less smile toward the patient, some patients do not have Health Social Security Agency, lack of socialization, lack of information for public knowledge about the self-registration procedure to Health Public Center of using Indonesia Health Card, very long queue when taking medicine at the public health center drugstore, and the doctor used to come late. The research problem is defined on the extent of the services given by the Setiabudi Public Health Center officers to the patients with Health Social Security Agency and Indonesia Health Card utilization. The research uses a qualitative approach. Data collection is done by interview, observation, and documentation techniques. The subject of this research is four informants consisting of the public health center chief, administrative division chief, patient, and Academic Lecturers at the Institute of Mandala Indonesia. The results signified that the criteria for the receiver of Indonesia health card are only allocated for those who are highly in need of the card. Finishing time is not punctual, its implementation is not fast, patients are waiting or queuing for a long time. Public Health Center sometimes out of medicine for the patients using Indonesia Health Card which lead to the patients searching for the drugs outside the public health center. Public Health Center has complete facilities and infrastructures for facilitating Health Social Security Agency and Indonesia Health Card. Health Workers know the field of the health sector and have skills in their health field. However, it is known that doctors have less attitude towards patients. Doctors are often arrived late, so patients are left waiting for a long time.Â